Abuse of Informed Consent - Monge, Julián (2019)
Informed consent is one of the great ethical achievements of humanity, but it is not always ethical to demand it. It is made to protect people who are subjects of experimentation, or who give private information for scientific research. It should only be required when at least one of these conditions exists.